Pengaruh Bermain Game Mobile Legend dan Komunikasi Interpersonal Terhadap Interaksi Sosial - Prasetyo, Dhimas Irga; Riyanto, Buddy; Sarungu, Lukas Maserona (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The aim of this study is to mitigate the influence of Mobile Legend play and interpersonal communication on social interaction among students. This research is quantitative. The type of research used is explanatory research. The research population is a student of the Faculty of Social Sciences and Political Sciences at the University of Slamet Riyadi. Number of samples: as many as 100 respondents with the non-probability sampling method with accidental samplings. Data collection techniques include questionnaires. Data analysis techniques using double linear regression. Interpersonal communication has a positive influence on the social interaction of students in the Faculty of Social Sciences and Political Sciences at the University of Slamet Riyadi. Playing online games and interpersonal communications have an impact on interaction between students in the Faculty of Social Science and Politics at the university.